Diatomáceas epilíticas indicadoras da qualidade de água na bacia do Rio Gravataí, Rio Grande do Sul, Brasil - Salomoni, Saionara Eliane (Universidade Federal de São Carlos, 2004)
Diatoms are amongst the most representative groups of algae in periphytic communities. There is evidence that epilithic diatom assemblages are good indicators of environmental condition since species composition and population abundances change in a more or less predictable way due to pollution or contamination of surrounding waters. The present study investigated limnological characteristics of the Gravataí River, RS, Brazil, following, in the course of two seasons, variations of physical, chemical and biological variables, between September 2000 and August 2002. Spatial and temporal changes in the structure and diversity of epilithic diatom communities were studied in order to be applied as water quality indicators. Sampling of epilithic diatoms from stones used as artificial substrates were carried out every three months, in six sites along the river. Climatic, hydrological physical and chemical variables were simultaneously analyzed. A marked seasonal variability was observed regardig both climate and hydrology. Seasonal variation in temperature was wide, with a range of 20°C between summer and winter seasons and a one order of magnitude variation in river discharge. The results evidenced that Gravataí River has two distinct portions, the Upper-Middle stretch, oligotrophic, oligo-mesosaprobic, being placed in Class 1 or 2 regarding, water uses according to CONAMA classification and the Low Stretch , meso-eutrophic, meso-polisaprobic, Class 2, 3 and 4. There is a gradient descontinuity in the Middle course caused by the discharge of heavily polluted residual waters from Porto Alegre city, resulting on increments of labile organic matter and increase of 3 to 50 times on DBO and faecal coliforms, respectively. A total of 169 taxons were recorded in the epilithic diatom assemblages of Gravataí River during the studied period. The species Cocconeis placentula, Achnanthes sp, Selllaphora seminulum and Eolimna minima were particularly abundant in the autumn, whereas Gomphonema parvulum, Eunotia pectinalis and Navicula radiosa reached the highest densities in the winter. It was also observed that Nitzschia palea and Sellaphora seminulum became gradually dominant and constant species in the Low stretch of the river, for being more tolerant to pollution. The use of a biotic index considering both environmental variables and the relative abundances of species, combined as indicative values, well represented the gradient and temporam changes observed..Comparing these indices with those calculated using the Regional Water Quality Index available from literature gave very similar values evidenced that the model might adequately describe the water quality in the rivers of Rio Grande do Sul.
Keywords: Bacillariophyceae; Bioindicadores; Diatomáceas; Estrutura de comunidades; Perifiton; Variação sazonal; CIENCIAS BIOLOGICAS::ECOLOGIA